Polymorphous adenocarcinoma of salivary glands. (August 2019) - Mimica, Ximena; Katabi, Nora; McGill, Marlena R.; Hay, Ashley; Zanoni, Daniella Karassawa; Shah, Jatin P.; Wong, Richard J.; Cohen, Marc A.; Patel, Snehal G.; Ganly, Ian
Highlights: PAC has an excellent survival, with a 5- and 10-year DSS of 98% and 94%. PAC patients do experience recurrence and tends to occur late. Long-term follow-up is indicated in patients with this pathology. Abstract: Objective: Polymorphous adenocarcinoma of salivary gland (PAC) is rare. Despite being described as a low risk histology, some patients develop regional and distant metastasis. More aggressive behavior has been attributed to a PAC subcategory called cribriform adenocarcinoma of minor salivary glands (CAMSG). We examined oncological outcomes of PAC. Patients and methods: Fifty-seven patients with PAC were identified from an institutional database of 884 patients surgically treated for salivary gland malignancies from 1985 to 2015. Detailed histopathological analysis was performed. Survival outcomes were calculated using the Kaplan-Meier method. Factors predictive of recurrence were identified using the Cox proportional hazard method. Results: Fifty-four (95%) had tumors of minor salivary gland origin; the most frequent location was the oral cavity in 41 (76%), specifically the hard palate in 32 (55%). Forty-six patients (81%) were clinical T1-T2; 3 (5%) had a clinically positive neck. Thirty-two patients (56%) were classified as PAC and 14 (25%) as CAMSG. Forty-four patients (77%) had surgery alone; 13 (23%) had surgery and postoperative radiotherapy. The 5- and 10-year overall survival and disease-specific survival were 88% and 79% and 98% and 94%, respectively (median follow up 84 [1–159] months); 5- and 10-year recurrence-free survival were 93% and 88%, respectively. Univariate analysis showed male sex, III/IV stage, and CASMG variant had increased incidence of recurrence but were not statistically significant. Conclusion: PAC of the salivary glands is an indolent disease with good survival outcomes. Recurrence is uncommon and tends to occur late. Long-term follow-up is indicated in patients with this disease.